Fifth Graders’ Interpretations of The Red Tree - Diane Barone; Rebecca Barone (Networks: An Online Journal for Teacher Research, 2017)
Fifth graders responded to a video of a picturebook, The Red Tree by Shaun Tan. They had not experienced explicit instruction in visual literacy and their responses served as a foundation for basic understanding of their analysis. We learned that they focused on four major areas: emotional aspects; visual qualities, summaries of the story; and a text focus. They understood the character’s emotions and were able to interpret many of Tan’s images.